ORGANIZATIONAL DEVELOPMENT OF MARKETING AND SALES MANAGEMENT SYSTEMS OF AGRICULTURAL ENTERPRISES - BILOSHAPKA, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to substantiating the organizational principles of management of marketing and sales activities of domestic agricultural enterprises. A logical-structural scheme for forming and functioning systems for distributing agrarian enterprise products on the market is proposed. The classification of the patterns of construction and operation of agricultural production distribution systems is substantiated. Critical aspects of the organization of the sale of agricultural products are considered, particularly those with a short shelf life and those with a long shelf life. It is substantiated that for the first category of products, the most effective is direct sales or the involvement of only one intermediary. In contrast, for the second category, long distribution chains are characteristic. The objective reasons affecting the development of such distribution channels are singled out, in particular, the difference in the levels of concentration and efficiency of capital. The influence of the size and volume of production on the choice of distribution channels and the role of stereotypical and behavioral patterns in the formation of the distribution system is emphasized. The need for rational management strategies for product distribution to ensure the economic efficiency of the enterprise is substantiated. The principles for improving an agricultural enterprise’s efficiency and financial condition at the stage of organizing the sale of its products are determined. The first principle is management based on the results of sales activities, which provides the possibility of responding to changes in the market. The second principle is the differentiation of distribution channels- different ways of delivering products to the market. The third principle is the adaptability of the sales system, which involves flexibility in switching between different distribution channels. Applying these principles helps reduce risks and improve efficiency in the market for the stable development of the enterprise.